Effectiveness of Program to Promote Screening for Diabetic Retinopathy among People with Diabetes at Wat Sothon Wararam Community Health Center - เจริญสิทธิชัย, พรทิพย์; บุญมาก, ปรีดาวรรณ (Journal of Health Science of Thailand, 2025)
This quasi- experimental research was conducted from October to December 2023 with the objective to assess the effectiveness of program to promote screening for diabetic retinopathy among people with diabetes. The purposive sampling was performed to recruit 50 participants who were divided into two groups: the control group receiving usual care and the experimental group receiving program to promote diabetic retinopathy screening developed by using health literacy framework to improve health literacy skills of participants including the promoting access of information of diabetic retinopathy, effective communication with the Line official account application and telephone as well as notification 1 day and 1 week in advance. The content valid index of the program and case record forms which proved by three experts was 0.98 and 0.95 respectively as well as the item objective congruence of diabetic retinopathy test was also proved which was 0.7-1.0, while the Cronbach Alpha coefficient of the test was 0.76. The baseline characteristics of the two groups were analyzed using descriptive statistic; and the Chi-square was used to test the homogeneity of them. The 95% confidence interval of relative rate of non -attendance diabetic retinopathy screening and attributable fraction were analyzed as well. The results showed statistical significance of increasing of diabetic retinopathy post test score (p<0.05). The rate of non-attendance diabetic retinopathy screening in the group of receiving program to promote diabetic retinopathy screening was significantly lower than the group of receiving usual care (3.83 times, 95%CI of RR=1.7-8.6). It was also found that the attributable fraction was 73.9%, indicating that this program was effective in reducing the rate of non-attendance diabetic retinopathy screening by 73.9%.